2011
DOI: 10.1007/978-3-642-19315-6_26
|View full text |Cite
|
Sign up to set email alerts
|

Hemispherical Confocal Imaging Using Turtleback Reflector

Abstract: Abstract. We propose a new imaging method called hemispherical confocal imaging to clearly visualize a particular depth in a 3-D scene. The key optical component is a turtleback reflector which is a specially designed polyhedral mirror. By combining the turtleback reflector with a coaxial pair of a camera and a projector, many virtual cameras and projectors are produced on a hemisphere with uniform density to synthesize a hemispherical aperture. In such an optical device, high frequency illumination can be foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…It is technically difficult to realize an instrument capable of acquiring thousands of images with different illumination and observation directions of the sample surface within reasonable time, so there is only few realized BTF setups. Portable BTF measurement setups are rare, but a few can be found that could be realized as portable ones [5,6,7,8,9,10,11]. Our instrument for BTF on site measurement was designed as a compact and portable system which tackles the dimension issues and acquisition speed enhancement by a combination of the parallelization of the illuminators and cameras with their mutual motions regarding the sample surface [1].…”
Section: The Btf Measurement Instrumentmentioning
confidence: 99%
“…It is technically difficult to realize an instrument capable of acquiring thousands of images with different illumination and observation directions of the sample surface within reasonable time, so there is only few realized BTF setups. Portable BTF measurement setups are rare, but a few can be found that could be realized as portable ones [5,6,7,8,9,10,11]. Our instrument for BTF on site measurement was designed as a compact and portable system which tackles the dimension issues and acquisition speed enhancement by a combination of the parallelization of the illuminators and cameras with their mutual motions regarding the sample surface [1].…”
Section: The Btf Measurement Instrumentmentioning
confidence: 99%
“…Mukaigawa et al . [MTK*11] designed a polyhedral mirror based on the geometric properties of ellipsoids for a design that allows the placement of objects at one focal point and a camera at the other to perform hemispherical confocal imaging.…”
Section: Basics and Related Workmentioning
confidence: 99%
“…In contrast to Mukaigawa et al . [MTK*11], we provide a user guided optimization pipeline for the derivation of the geometric configuration.…”
Section: Basics and Related Workmentioning
confidence: 99%
“…The measurement is usually made in a laboratory under well-controlled conditions. The widely used method relies on imagebased bidirectional reflectance distribution function (BRDF) measurement [2,10,12,13] by capturing many images of the material sample with different known light directions. Moreover, joint shape and reflectance recovery using images is even more challenging, particularly under uncontrolled illuminations.…”
Section: Introductionmentioning
confidence: 99%